Tamiḻ ilakkiya varalāṟu, Ki. Pi. 1 nutal 1100 - Varatarāja Aiyar, E. S. (Annamalai University Tamil series., 1979)
On the contributions of Jains, Buddhists, and Vaishnavites to Tamil language and literature.